Technical Efficiency in Cashew Nut Production in Kilifi County, Kenya - R.K, Koech; S.M, Mwakubo; P.M, Nyangweso (IJRDO - Journal of Business Management, 2016)
The agricultural sector continues to be an important pillar of the coastal economy in Kenya.Cashew nuts together with coconuts are the principal cash crops grown in Kilifi County. Eventhough efforts have been made to improve productivity in the smallholder cashew sector, notmuch has been realized and productivity continues to stagnate. It seems that productiontechnologies generated in research institutions have had minimal impact on efficiency andresource productivity. This study was therefore carried out with the main aim of analyzing theeconomic factors that influence production of cashewnut in Kilifi County. This was done bymeasuring the technical efficiency of cashew nut production and isolating the determinants ofthese efficiencies. The study used ordinary least squares (OLS) and maximum likelihoodestimates (MLE) procedures to estimate parameters of identified input variables. The model alsoestimated technical efficiencies of individual farmers. Results showed that land area undercashew and extension service were significant determinants of output at five one per cent level ofsignificance respectively while labour was significant at ten per cent